The Paradoxical Success of UNCLOS Part XV: A Half-hearted Reply to Rosemary Rayfuse - Serdy, Andrew (Victoria University of Wellington Law Review, 2005)
In his reply to Rosemary Rayfuse's article, "The Future of Compulsory Dispute Settlement under the Law of the Sea Convention", Andrew Serdy addresses some of the criticisms that have been levelled at the Part XV dispute resolution provisions of the United Nations Convention on the Law of the Sea (UNCLOS). He concludes that despite being little used, the Part XV provisions remain pivotal to UNCLOS and its related treaties, and if anything are becoming more so